THE INFLUENCE OF FINANCIAL LITERACY, ENTREPRENEURIAL ORIENTATION, AND PRODUCT INNOVATION ON MSME PERFORMANCE IN TAMAN JAYAWIJAYA MOJOSONGO - Ranjani, Efti Adellia; Wibowo, Edi (LPPM STIE EKA PRASETYA, 2025)
MSME performance is the results of achievements ranging from sales, profits, consumer satisfaction, efficiency and innovation. The development of MSMEs requires business actors to be wiser in managing their finances and performance as the main key to the success of a business. This research aims to test the significance of the influence of financial literacy, entrepreneurial orientation and product innovation on the performance of MSMEs in Taman Jayawijaya Mojosongo. The data source for this research is primary data. Research data was collected using a questionnaire. The data analysis technique used is multiple linear regression analysis, t test, F test, and coefficient of determination. The results of this research are that financial literacy has a significant effect on the performance of MSMEs in Taman Jayawijaya Mojosongo, entrepreneurial orientation has no significant effect on the performance of MSMEs in Taman Jayawijaya Mojosongo, and product innovation has a significant effect on the performance of MSMEs in Taman Jayawijaya Mojosongo.